O04 NCEPOD – alcohol related liver disease care: 'measuring the units' 10 years on. (20th September 2022) - Allison, Michael; Smith, Neil; Juniper, Mark
Abstract : The 2013 NCEPOD report 'Measuring the Units' reviewed the care of patients who died with alcohol-related liver disease (ArLD) in 2011. It highlighted that the care of patients who died of ArLD was less than good in more than 50% of cases reviewed. Given the ongoing concerns about the variation in outcomes of patients with ArLD, a Survey of the care of patients admitted to hospital with ArLD was commissioned by NCEPOD. Methods: All Acute Trusts in England, Wales and Northern Ireland were sent the Survey, which required completion based on Trust data and Lead Gastroenterologist/Hepatologist input. The questions covered numbers of admissions and mortality, alcohol screening and withdrawal management, the presence and constitution of an Alcohol Care Team (ACT), triage of decompensated ArLD patients to Gastroenterology/Hepatology and use of the BSG/BASL chronic liver disease care bundle, as well as escalation of care. In view of the impact of COVID-19, the Survey was sent round to Acute Trusts in January 2021 interrogating information from 2019. Results: NCEPOD received responses from 145 Acute Trusts including District General Hospitals, regional Liver Units as well as Liver Transplant Units. This included 20, 876 ArLD admissions and 2481 deaths in hospital, constituting 11.9% of admissions), with a wide variation in the numbers of reported admissions and deaths between Trusts. The use of symptom-triggered alcohol withdrawal scale (CIWA-Ar) was only 9.9% in the original report, but was employed on specific wards in 88.2% of Trusts in this Survey. The presence of a multidisciplinary ACT increased from 23.2% of Trusts in 2011 to 51.9%, although only 20% of Trusts responding had a Consultant Lead with dedicated sessions. 78% of Trusts stated that they triage patients with decompensated cirrhosis to a Gastroenterologist/Hepatologist and 70% of responding Trusts stated that they used BSG/BASL decompensated chronic liver disease care bundle. The responding clinician reported that it was subjectively more difficult to get patients with decompensated ArLD rather than other forms of cirrhosis into Critical Care in 28.3% of Trusts. Only 23% of ArLD patients who died had coded evidence of palliative care input. Conclusions: This Survey compares specific aspects of care in patients with ArLD between 2011 and 2019 and indicates that there have been noteworthy improvements in certain areas of care provision, but also points to where attention is required in order to achieve consistent, high-quality care for this patient group, who have a high in-patient mortality.